Estudio en estructuras de hormigón armado Velocidad de ultrasonidos y resistencia a compresión - Alcañiz-Martínez, Jesus; Louis-Cereceda, M.; Sánchez-Medrano, F. J.; Lasheras-Estrella, A. (Revista Científica, 2015)
So far, much of the research conducted to estimate the compressive strength of reinforced concrete elements of our structures have been made based on checkups witness many samples drawn from these elements. By this investigation 185 real cases of reinforced concrete structural elements are studied by a structural check based on the correlation of results between the ultrasonic velocity (V) and compressive strength (R). The study was developed taking into account the location of the building relative to the shoreline and the age of the structure. Subsequently, a statistical analysis to the data obtained is performed. This work has achieved a scientific method of analysis of the two test methods and necessary for a full structural check, correlation between them and most innovative process, making mathematical formulas and graphs mapping tools which demonstrate the effectiveness of the procedure, which is proposed as a contribution to policy.